Olmutinib Induced Lichen Planus Like Eruption - Oh, Seung Hwan (Ann Dermatol, 2018)
Drug induced lichen planus like eruption is an uncommon cutaneous adverse effect of several drugs. This appears symmetric eruption of erythematous or violaceous plaques resembling lichen planus on the trunk and extremities. A 50-year-old male presented with scaly, violaceous plaques and dusky brown macules on whole body. For four months, the patient was treated with olmutinib, an oral, third-generation epidermal growth factor receptor-tyrosine kinase inhibitor. In May 2016, olmutinib received its first global approval in South Korea for the treatment of patients with locally advanced or metastatic epidermal growth factor receptor T790M mutation-positive non-small cell lung cancer. The biopsy specimen from the patient showed features of lichen planus. We diagnosed him with olmutinib-induced lichen planus like eruption. He was treated with oral methylprednisolone and topical desoxymethasone 0.25% ointment. At the same time, olmutinib dose was decreased to three-fourths of this patient's starting dose. After that, the cutaneous lesions improved.